The black stallion returns : a storybook based on the movie - Farley, Walter, 1915- (New York : Random House, 1983)
After the Black is claimed by its rightful owner, a great desert chieftain from across the sea, Alec crosses the desert amid many dangers in search of the stallion.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction